Maqasid Kafa'ah for Family Resilience in The Era of Disruption 5.0 Fiqh Perspective - Nurliana; Yusrial; Norcahyono; Nur, Syamsiah (Sekolah Tinggi Agama Islam Taruna Surabaya, 2025)
The era of disruption 5.0 is an era of massive development of information technology. Able to change culture, lifestyle patterns, family order quickly, the changes that occur tend to make family life unstable, not sustainable, differences in attitudes, changes in lifestyle, commitment as an external attack due to cultural shifts so that family life is unable to survive, increasing divorce rates, violence in the family. Generally, people who have families prioritize kafa'ah in choosing a partner, especially aspects of social status, wealth, career and position. From the existing phenomenon, it is necessary to implement maqasid kafa'ah towards family resilience of the era disrution 5.0 the Fiqh Perspective. The research method used is library research, the using triangulation method by classifying data, presenting and drawing conclusions and analyzing it through content analysis. Finddings reseach: First, it is necessary to choose partner who is as good as aspects of piety and noble morals, leading to realizing a sakinah, mawaddah family life while implementing Islamic values ​​in the family. Second, kafa'ah makes the family journey process quality. Third, a strong, resilient, understanding, and implemented Islamic generation in life was born